Tindak Pidana Peretasan Media Sosial Oleh Anak Dalam Putusan Nomor 53/PID.SUS-ANAK/2019/PN MKS Perspektif Hukum Pidana Islam - Nur, M Devin Putra; Saepullah, Usep; Royani, Yayan Muhammad (Kartika: Jurnal Studi Keislaman, 2025)
This study examines the criminal act of social media hacking by a minor, as addressed in Decision Number 53/Pid.Sus-Anak/2019/PN Mks. The research focuses on how Indonesian positive law and Islamic criminal law respond to hacking committed by a child, and how judges determine appropriate sanctions. Using a normative juridical method, the study analyzes court rulings, the ITE Law, the Juvenile Justice System Law, and Islamic jurisprudence (fiqh jinayah). The findings show that the offender received non-custodial sanctions, namely guidance and vocational training, in line with restorative justice aimed at rehabilitation. In Islamic law, such an act falls under taʿzīr a discretionary crime whose punishment is determined by the judge based on public interest. The study recommends further integration of Islamic principles into Indonesia’s juvenile justice system, particularly in addressing cybercrimes involving minors, in order to protect children's rights and ensure their future reintegration into society